(untitled) (Journal of the College of Basic Education, 2024)
The study aimed to identify psychological empowerment and the professional self among kindergarten teachers. It also aimed to identify the relationship between psychological empowerment and the professional self among kindergarten teachers. The descriptive, correlational approach was used to suit the aim of the study, and a measure of psychological empowerment and the professional self was built by the researcher in accordance with the scientific steps in constructing psychological measures. After verifying the psychometric properties of the two scales, the two scales were applied to the study sample, which consisted of (190) kindergarten teachers in government kindergartens in Baghdad Governorate for the academic year (2023-2024). The results of the study indicated that kindergarten teachers have psychological empowerment and a professional self, and there is a correlational and statistically significant relationship between psychological empowerment and a professional self. The researcher presented a number of recommendations, including based on the results the study reached in terms of the relationship between psychological empowerment and the professional self. This result can be used in future research and studies to raise the level of psychological empowerment as well as the professional self.